Control and observation of DNA nanodevices - Machinek, R; Robert Machinek (2014)
The uniquely predictable and controllable binding mechanism of DNA strands has been exploited to construct a vast range of synthetic nanodevices, capable of autonomous motion and computation. This thesis proposes novel ideas for the control and observation of such devices. The first of these proposals hinges on introducing mismatched base pairs into toehold-mediated strand displacement – a fundamental primitive in most dynamic DNA devices and reaction networks. Previous findings that such mismatches can impede strand displacement are extended insofar as it is shown that this impediment is highly dependent on mismatch position. This discovery is examined in detail, both experimentally and through simulations created with a coarse-grained model of DNA. It is shown that this effect allows for kinetic control of strand displacement decoupled from reaction thermodynamics. The second proposal improves upon a previously presented strand displacement scheme, in which two strands perform displacement cooperatively. This scheme is extended to be cascadable, so that the output of one such reaction serves as input to the next. This scheme is implemented in reaction networks capable of performing fundamental calculations on directed graphs. The third proposal is exclusively concerned with a novel observation methodology. This method is based on single-molecule fluorescence microscopy, and uses quantum dots, a fluorescent type of semiconductor nanocrystal, as a label. These quantum dots display a set of characteristics particularly promising for single-molecule studies on the time- and length scales most commonly encountered in DNA nanotechnology. This method is shown to allow for highly precise measurements on static DNA devices. Preliminary data for the observation of a complex dynamic device is also presented.